Impact of Consumers’ Perceptions on Uses of Internet banking in Burdwan District - Singha, Souvik; Dasgupta, Tanmoy (IJRDO - Journal of Business Management, 2018)
Consumers’ adoption of a technology has become a significant measure of the success of new technology. Internet banking is the latest and most innovative service and is the new trend among the consumers. This research able to determines the factors influencing the consumers’ perception of internet banking in Burdwan District, West Bengal, India. In this study survey based questionnaire was formulated. For measuring the accuracy of data, reliability test was conducted and hence investigated the influence of perceived usefulness, perceived ease of use and perceived reliability.